Using Wargames In The Classroom To Teach Historical Thought - Burenheide, Brad (Teaching History: A Journal of Methods, 2007)
The brigade moved stealthily along the trees preparing to enter the broad span of pastoral fields that separated them from two entire corps of Union infantry. There was not too much to see as the artillery barrage had left the field almost entirely enveloped in a shroud of smoke. Yet, as occasional puffs of wind blew columns of haze so that a brief glimpse of the opposing ridge could be seen, the commanders were having second thoughts. The Confederate commander expressed her opinion: "Perhaps General Longstreet was correct and we would have been better off attacking around their left flank. Move the army towards Little Round Top as we did on the 2nd and let's try our luck there." Thus, the Battle of Gettysburg changed entirely on that fateful day in March 2006.